Economic Empowerment of School Dropouts Through the Campus Impact Program's Barbering Training - Haposan Laia; Kalvin Alexander Hulu; Yusmalinda (Yayasan Cerdas Pedia Indonesia, 2026)
Unemployment among the school dropout youth is a crucial issue in Sinaksak Beringin Village. This community service program specifically aims to empower five unemployed youths through barbering training based on the Campus Impact program. Using Participatory Action Research and community development methods, this activity was conducted over four months. The comprehensive curriculum includes modern barbering techniques, pathogen mitigation, and entrepreneurial management. This training prioritizes direct practice to accelerate basic understanding. Evaluation results demonstrate a perfect economic absorption success rate. Three participants successfully established independent micro enterprises, while the other two were absorbed as professional workers at local barbershops. Besides delivering financial independence, this intervention also successfully restored the confidence and social status of the participants within their community. In conclusion, this vocational approach is highly effective in efforts to alleviate structural poverty. To guarantee business sustainability, advanced mentoring regarding digital marketing literacy and collective capital access is highly recommended hereafter.